Evaluasi Pembelajaran Model CIPP Sebagai Alat Ukur Keberhasilan Mengajar Guru Pendidikan Agama Kristen - Hutapea, Rinto Hasiholan (Fakultas Ilmu Keguruan dan Pendidikan, Universitas Kristen Indonesia, 2022)
This manuscript intends to examine the learning evaluation of the CIPP (Context, Input, Process, Product) model as a measuring tool that can be used by Christian Religious Education teachers to determine teaching success. Literature review is the approach used to achieve the objectives of this study. The results of the study revealed that the success of teaching Christian Religious Education teachers cannot ignore aspects of the learning context. Where Christian Religious Education teachers need to pay attention to the media and learning facilities available and used. The availability of learning facilities, the understanding of students and teachers in the use of media, as well as the quality of the material delivered in the classroom are inputs that also need to be considered by the teacher. This aspect of input is closely related to the competence of the Christian Religious Education teacher himself. Where teachers are required to have the ability to use facilities, learning media, and the ability to master learning materials. This aspect of the process becomes the next important part as a measure of the success of teaching Christian Religious Education teachers. Especially the evaluation of each learning implementation process. Be it evaluation of the process of teacher teaching activities, evaluation of the process of using and utilizing media and learning facilities, as well as evaluating obstacles and obstacles in learning. Finally, the product aspect which includes the results of the implementation of learning, as well as the impact of the knowledge possessed by students and teachers are aspects that encourage the success of teaching Christian Religious Education teachers. Where the results of the implementation of learning in the classroom can be seen from the level of efficiency and effectiveness of teaching teachers. Whether it is related to the use of effective learning methods and media, or subject matter that is easy to understand and accept by students.Manuskrip ini bermaksud untuk mengkaji evaluasi pembelajaran model CIPP (Context, Input, Process, Product) sebagai alat ukur yang dapat digunakan oleh guru Pendidikan Agama Kristen untuk mengetahui keberhasilan mengajar. Literatur review menjadi pendekatan yang digunakan untuk mencapai tujuan dari penelitian ini. Hasil penelitian mengungkapkan bahwa keberhasilan mengajar guru Pendidikan Agama Kristen tidak dapat mengabaikan aspek konteks pembelajaran. Dimana guru Pendidikan Agama Kristen perlu menaruh perhatian pada media dan sarana pembelajaran yang tersedia maupun yang digunakan. Ketersediaan fasilitas pembelajaran, pemahaman peserta didik dan guru dalam penggunaan media, serta kualitas materi yang disampaikan dalam kelas menjadi input yang juga perlu diperhatikan oleh guru. Aspek input ini berkaitan erat dengan kompetensi guru Pendidikan Agama Kristen itu sendiri. Dimana guru dituntut untuk memiliki kemampuan dalam menggunakan fasilitas, media pembelajaran, maupun kemampuan dalam menguasai materi pembelajaran. Aspek proses menjadi bagian penting berikutnya sebagai alat ukur keberhasilan mengajar guru Pendidikan Agama Kristen. Khususnya evaluasi setiap proses pelaksanaan pembelajaran. Baik itu evaluasi proses aktivitas mengajar guru, evaluasi proses penggunaan dan pemanfaatan media maupun sarana pembelajaran, serta evaluasi hambatan dan kendala-kendala dalam pembelajaran. Terakhir, aspek produk yang meliputi hasil pelaksanaan pembelajaran, serta dampak pengetahuan yang dimiliki peserta didik dan guru menjadi aspek yang mendorong keberhasilan mengajar guru Pendidikan Agama Kristen. Dimana hasil pelaksanaan pembelajaran di kelas dapat dilihat dari tingkat efisiensi dan efektivitas mengajar guru. Baik itu berkaitan dengan penggunaan metode dan media pembelajaran yang efektif, maupun materi pelajaran yang mudah dipahami dan diterima oleh peserta didik.